(untitled) (Applied Biological Research, 2023)
Secondary bacterial infections and the emergence of drug resistant microbial strains are two consequences concomitant with COVID-19 pandemic. It demands novel antibacterial drugs to treat secondary bacterial diseases. The present study reveals that the ethyl acetate extract of the leaves of A. latifolium has antibacterial efficacy against six pathogenic bacteria, viz., Bacillus cereus, Staphylococcus aureus, Proteus mirabilis, Pseudomonas aeruginosa, Escherichia coli and Klebsiella pneumonia, reported to be infecting COVID-19 patients. Molecular docking and FTIR studies have been used to find out the lead molecules of the extract. The triterpenoids 22-hydroxyhopane and 3β acetoxy-21α-H-hop-22(29)ene have shown high binding affinity (binding that the phytocompounds present in A. latifolium may serve to combat COVID-19 associated ailments.